2012
DOI: 10.1111/j.1369-1600.2012.00436.x
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine increases sucrose self‐administration and seeking in rats

Abstract: Associations between nicotine in cigarettes and food consumption may alter the incentive value of food such that food cue-reactivity is exaggerated during abstinence from smoking. This effect may contribute to the weight gain associated with cessation of smoking. We examined the effects of nicotine (0.4 mg/kg base SC) paired (NPD) or unpaired (NUP) with 10 % sucrose self-administration (0.2 ml/delivery, 1h/day for 10 days) on self-administration response rate and intake as well as sucrose cue-reactivity follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 36 publications
2
18
1
Order By: Relevance
“…The reduction in latencies following nicotine administration (Figure 4, left) thus suggests that nicotine enhanced the reinforcing efficacy of sucrose pellets. These data are consistent with reports of nicotine-induced enhancement of reinforcer efficacy for appetitive reinforcers or food-related cues (see Donny et al 2011) in both rats (Grimm et al 2012; Raiff and Dallery 2006; Wing and Shoaib 2010) and humans (Epstein et al 1992; Perkins 1992). …”
Section: Discussionsupporting
confidence: 91%
“…The reduction in latencies following nicotine administration (Figure 4, left) thus suggests that nicotine enhanced the reinforcing efficacy of sucrose pellets. These data are consistent with reports of nicotine-induced enhancement of reinforcer efficacy for appetitive reinforcers or food-related cues (see Donny et al 2011) in both rats (Grimm et al 2012; Raiff and Dallery 2006; Wing and Shoaib 2010) and humans (Epstein et al 1992; Perkins 1992). …”
Section: Discussionsupporting
confidence: 91%
“…Numerous studies have shown that acute noncontingent nicotine administration increases responding for sucrose under fixed-ratio [84] and progressive-ratio schedules during limited access to nicotine [8587]. In contrast, NSA in the present study only produced a transient decrease in sucrose intake.…”
Section: Discussioncontrasting
confidence: 71%
“…We compared the magnitude of “incubation of saccharin craving” shown in this study to “incubation of sucrose craving” shown in a previous experiment (Grimm, Ratliff, North, Barnes, & Collins, 2012). The procedure used in the previous experiment was identical to the present experiment except for the following four differences.…”
Section: Resultsmentioning
confidence: 95%
“…We compared the magnitude of “incubation of saccharin craving” shown in this study to “incubation of sucrose craving” shown in a previous experiment (Grimm, Ratliff, North, Barnes, & Collins, 2012). The effects of reinforcers (saccharin vs. sucrose) and forced abstinence period on active lever responses, inactive lever responses, cue-presentations, and photobeam breaks in the testing phase were evaluated by two-way ANOVAs using REINFORCERS (saccharin or sucrose) and ABSTINENCE-DAYS (Day 1 or Day 30) as between-group factors.…”
Section: Methodsmentioning
confidence: 95%